Career of evil - Galbraith, Robert (New York Mulholland Books/Little, Brown and Company, 2015)
When a woman's severed leg is delivered to Robin Ellacott, her boss, private detective Cormoran Strike, looks into his past to determine who is responsible.
Robert Galbraith : pseudonyme de J.K. Rowling.-When a mysterious package is delivered to Robin Ellacott, she is horrified to discover that it contains a woman's severed leg. Her boss, private detective Cormoran Strike, is less surprised but no less alarmed. There are four people from his past who he thinks could be responsible -- and Strike knows that any one of them is capable of sustained and unspeakable brutality. With the police focusing on the one suspect Strike is increasingly sure is not the perpetrator, he and Robin take matters into their own hands, and delve into the dark and twisted worlds of the other three men. But as more horrendous acts occur, time is running out for the two of them ... A fiendishly clever mystery with unexpected twists around every corner, Career of Evil is also a gripping story of a man and a woman at a crossroads in their personal and professional lives ...
Contain bibliographical references (pages 493-497).
106288
Keywords: Private investigators -- England -- London -- Fiction; Criminal investigation; England -- London; Mystery fiction; Detective and mystery fiction; Thrillers (Fiction)